FAKTOR-FAKTOR YANG MEMPENGARUHI PERGANTIAN KANTOR AKUNTAN PUBLIK PADA PERUSAHAAN GO PUBLIC DI INDONESIA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2007-2012) - Farid, Zenuar; Pamudji, Sugeng (Diponegoro Journal of Accounting, 2014)
Independence of the public accounting firm will fade when the suspect had long-standing relationships with its client. One way to keep independence auditor is to make the turn public accounting firm. Several previous studies showed the results of different studies. This study aims to examine and obtain empirical evidence about the factors that affect the company went public did turn public accounting firm in Indonesia. Factors used include audit fee, financial distress, share growth, audit delay. The study is a population of companies listed on the Stock Exchange in the year 2007-2012. The total sample is 115 using purposive sampling method. Hypothesis testing is performed using logistic regression using SPSS 16 application. The results of this study are audit delay have significant effect on the change of KAP on manufacturing companies in Indonesia. While other factors such as fee audit, financial distress, share growth, has no significant effect on the change of KAP on manufacturing companies in Indonesia.